Evaluation of the Green bean variety candidate BU-16 - Györgyi, Gyuláné (Acta Agraria Debreceniensis, 2008)
This study presents the results of the variety comparison trials conducted with the French bean variety candidate BU-16 on sandy soil, during two years at the Research Center of the University of Debrecen. The outstanding characteristics of this variety candidate are the early maturity, the showy pods (yellow, straight, cylindrical cross-section „pencil bean”) and the high yield potential. The experiments were conducted with a randomized design, with five varieties and four replications. The varieties (of which two are foreign and three are domestic) were as follows: BU-16 fj, Maxidor, Paridor, Hungold and Budai piaci. The individual plots were 2 m wide and 4 m long. The seeds were sown at a density of 30 germs per m2, with a row spacing of 50 cm. The following parameters were taken: time of flowering, time of green maturity, plant height, height of the lowest pod above ground level, number of pods per plant, distribution of the pods by the state of development (20 plants), usable pod length (1 kg of standard crop-yield), yield per hectare based on the number of plants per plot. The experiments were evaluated statistically with Excel and SPSS softwares. Results obtained with the variety candidate BU-16: – The time from the emergence to green maturity is 45 to 46 days, which is short as compared with the other cultivars studied. – Plant height is 38cm (two years average), which is among the highest ones, together with Paridor. – The pods are set high above the ground level similarly to Paridor, the height of the lowest pod is 19 cm. – The average number of pods per plant is 13 (two years average) similarly to Paridor and to Maxidor. – The distribution of pod size in 2007 is as follows: 68% of the pods of BU-16 is of the standars size, which is a good rate. The value of this trait for the other varieties is 60 to 63%, except for Paridor, the value of which is similar to that of BU-16. – The usable pod length (10 to 14 cm) is 63% in 2007 and 84% in 2006. Similar pod length rates were obtained for Maxidor, while the rate for Paridor is as high as 91%. – The total yield and the standard yield of BU-16 is among the highest ones. According to the results obtained and presented above, the variety candidate BU-16 is the earliest maturing among the varieties tested with high yield potential which, however, is not significantly different from that of the others. Significant differences can only be detected in plant height and the number of pods per plant. Considering the results, BU-16 is to be further tested.